Pembelajaran Iklan Menggunakan Multimedia Interaktif Berbasis Problem Based Learning - Seputra, I Gede Dika; Kristiantari, Maria Goreti Rini; Werang, Basilius Redan (Jurnal Media dan Teknologi Pendidikan, 2025)
This research was motivated by the limited advertising learning media in elementary schools, which has an impact on low student learning outcomes. The purpose of this study was to develop valid, practical, and effective PBL-based interactive multimedia to improve learning outcomes in advertising.  This research is a type of development research with the ADDIE model. The trial subjects in this study consisted of 2 material experts, 1 learning design expert, 1 media expert, 3 individual trial students, 9 small group trial students, 1 practicality test teacher, and 32 effectiveness trial students. The data collection techniques used in this study were questionnaires and tests using questionnaire instruments and multiple choice test questions. The results of this study state that: (1) PBL-based interactive multimedia obtained a validity of 94.50% on the content of learning mutants, 90.62% on learning media, and 90.90% on instructional design with very good qualifications. (2) PBL-based interactive multimedia is categorized as very practical with practicality results of 90.83% in individual tests, 90.55% in small group trials, and 97.91% in teacher practicality tests with very good qualifications (3) Hypothesis testing obtained a two-tailed significance value of 0.000 < 0.05, so it can be concluded that there is a significant difference in the class before and after being taught PBL-based interactive multimedia in Indonesian language subjects on advertising material. Overall, the results showed that PBL-based interactive multimedia is very feasible to be applied in the learning process and has implications for the development of interactive multimedia in educational innovation.